Toward Better Medical Diagnosis: Tissue Optical Clearing - Omnia, Hamdy; Rania, M. Abdelazeem (Journal of Public Health International, 2020)
Reaching efficient, safe and painless medical diagnosis procedure is a very valued goal for many research areas. Despite the great advantages of using optical imaging techniques in medical diagnosis including high safety and relative simplicity, it still suffers from relatively low resolution and penetration depth in the multiple scattering mediums such as biological tissues. Therefore, researchers began to devise ways to reduce the scattering properties of the tissue, hence increasing the imaging contrast. Optical clearing concept is introduced to do this job. This technique can reduce tissues scattering properties by using high refractive index chemicals, thus making the tissue transparent by equalizing the refractive index through that medium. In this paper, theory and techniques of optical clearing method are illustrated utilizing its benefits for deep imaging of different body tissues and organs.
Keywords: optical clearing; tissue scattering; medical imaging; diagnosis